Mahuang-Fuzi-Xixin Decoction Reverses Depression-Like Behavior in LPS-Induced Mice by Regulating NLRP3 Inflammasome and Neurogenesis - Wen Jing; Shanshan Song; Hong Sun; Ying Chen; Quan Zhao; You Zhang; Guoliang Dai; Wenzheng Ju (Neural Plasticity)
Evidence suggests that inflammation and neurogenesis play an important role in major depressive disorder (MDD). Mahuang-Fuzi-Xixin decoction (MFX), as the traditional Chinese prescription, has been widely applied for asthma, migraine, and MDD in clinics. However, the effects of MFX on the potential mechanism in MDD are still unclear. Hence, the present study is aimed at exploring whether the antidepressive effect of MFX is connected to the anti-inflammatory and promoting neurogenesis. Besides, lipopolysaccharide (LPS) of Gram-negative bacteria can induce depressive-like behaviors. We demonstrated that administration of MFX corrected the depressive-like behaviors in LPS-induced mice and significantly decreased the expression of IL-1β in the hippocampus. LPS injection induced a significant increase in the levels of NLRP3, cleaved caspase-1 p20, and ASC in the hippocampus, as well as Trx-interacting protein (TXNIP), and MFX could reverse this change. What is more, treatment of MFX increased the level of doublecortin (DCX), brain-derived neurotrophic factor (BDNF), and tropomyosin-related kinase receptor B (TrkB) in the hippocampus which means that MFX could promote the neurogenesis. In conclusion, the study indicates that MFX relieves a depressive-like state in LPS-induced mice through the inhibition of the NLRP3 inflammasome and the enhancement of the neurogenesis pathway.